1990
DOI: 10.1002/mrc.1260280206
|View full text |Cite
|
Sign up to set email alerts
|

13C CP‐MAS study of the polymorphs of naphthazarin and of some methyl derivatives

Abstract: The high-resolution 13C solid-state NMR spectra of naphthazarin polymorphs and some of its derivatives having methyl substituents are discussed. Differences observed between the spectra of the A and B forms and that of the C modification of naphthazarin are explained by invoking hydrogen-bonding effects. The 2-methyl and 2,fdimethyl derivatives show spectra consistent with their x-ray-determined structure as being mainly composed of the tautomer bearing the substituents on the quinonoid ring. The 2,7-dimethyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…IR (cm −1 ): 2962 (ν C-H ), 1594 (ν C O ), 1404, 1594 (ν C CAr ), and 1214 (ν C-O ). Doubling of some signals on 13 C NMR was reported for this molecule and can be explained by the presence of polymorphs as described by Olivieri et al (1990). 1 H NMR (300 MHz, chloroform-d) δ 0.70 (t, J 7.…”
Section: 8-dihydroxysupporting
confidence: 55%
See 1 more Smart Citation
“…IR (cm −1 ): 2962 (ν C-H ), 1594 (ν C O ), 1404, 1594 (ν C CAr ), and 1214 (ν C-O ). Doubling of some signals on 13 C NMR was reported for this molecule and can be explained by the presence of polymorphs as described by Olivieri et al (1990). 1 H NMR (300 MHz, chloroform-d) δ 0.70 (t, J 7.…”
Section: 8-dihydroxysupporting
confidence: 55%
“…13 C NMR (75 MHz, ). Doubling of some signals on 13 C NMR was reported for this molecule and can be explained by the presence of polymorphs as described by Olivieri et al (1990). 1 H NMR (300 MHz, chloroform-d) δ 0.97 (s, 18H, 6CH 3 ), 2.58 (s, 4H, 2CH 2 ), 6.92 (s, 2H, 2CH Ar ), 12.55 (s, 1H, OH), and 13.27 (s, 1H, OH).…”
Section: 8-dihydroxymentioning
confidence: 53%
“…Further comparisons of polymorphs A, B and C showed that the O-H...O intermolecular hydrogen bond was detected in the latter structure. The crystallographic analysis combined with available solid state NMR data provided information that at room temperature there is a rapid intramolecular proton exchange in the hydrogen bridge in all three Naphthazarin polymorphs [ 23 , 24 , 25 , 26 ]. The IR and Raman spectra were recorded for Naphthazarin confirming the presence of the intramolecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The change in the anisotropy values is controlled by relative differences among individual π P᎐O bond orders. 32 Hence, the described increase of ∆σ accompanies the increase of π electron density along the involved bond produced by a smaller contribution of the (TMPPO-H) ϩ structure with weaker proton donors. Thus, this effect should be the result of a smaller degree of hydrogen transfer when the substituted phenol increases its pK a value.…”
Section: Solid-state Studiesmentioning
confidence: 94%